MINIMISING ELECTRICITY COSTS BY DEVELOPING AN EFFECTIVE COMBINATION OF ALTERNATIVE ENERGY SOURCES - Steyl, Janine; Yadavalli, Venkata S.S. (The South African Journal of Industrial Engineering, 2020)
This study evaluates the high electricity costs faced at a carpet manufacturing company. Research was conducted by focusing on the supply and availability of electricity in South Africa and alternative energy sources. Modelling methods were investigated to determine an appropriate approach to solving the high-cost problem at the company to ensure that the model could be reused for similar scenarios. The findings provide an electricity minimisation solution that requires the installation of a solar system. Using generated solar energy, and consuming generator power to maintain optimal monthly municipal thresholds, electricity costs would be reduced by over R100 000 monthly.